ANALISIS LAJU KOROSI PADA BAJA ST-37 DENGAN VARIASI TEMPERATUR LINDI RESIDU SAMPAH DAN KETEBALAN CAT: CORROSION RATE ANALYSIS OF STEEL ST-37 WITH VARIATION OF TEMPERATURE LEACHATE AND PAINT THICKNESS - Kurniawan, Irfan Nur Hanif; Nugroho, Pipit Wahyu (Jurnal Teknik Mesin, 2024)
Efforts are made to improve the efficiency of waste transportation at TPS by making a belt conveyor machine. Problems on the part of the machine made of steel that is contaminated with garbage water (leachate) so that it can cause corrosion. To slow down the occurrence of corrosion, painting is done on all parts of the belt conveyor machine, especially on parts of the machine made of steel.  This research was conducted by immersing ST-37 steel (as the material of the conveyor belt machine parts made of steel) into the leachate solution with variations in waste residue leachate temperature with 35 ℃, 45 ℃, and 55 ℃ and iron paint thickness with variations of 15μm, 25μm, and 40μm. The corrosion rate was tested using the weightloss method. The corrosion rate study lasted for 5 weeks at the Malang State Polytechnic Materials Test Lab. The results showed that changes in waste residue leachate temperature affect the corrosion rate of steel, namely the higher the temperature, the higher the corrosion rate value. The variation of paint thickness on the steel as a coating also has a significant effect on the corrosion rate, the thicker the paint, the slower the corrosion rate. The interaction that occurs between temperature and paint thickness is directly proportional because the higher the temperature the higher the corrosion rate value but the value tends to decrease due to differences in paint thickness.